Effect of water and sport beverage intake on biochemical and physiological variables in trained wrestlers - Rashidlamir, A.; Goodarzi, M.; Mirzaee, B.; Zandi, S. (Medicina dello Sport, 2013)
Methods. Twenty-one young trained freestyle wrestlers (mean age: 22.29+0.9 yr, weight: 75.45+12.9 kg and BMI 21.23+2.60) volunteered to participate in this research and were randomly divided into three groups: Group 1 (0.1 g D-glucose per 1 kg of body weight), Group 2 (water) and Group 3 (non-beverage). The subjects were required to perform a wrestling-technique based circuit exercise (WTBCE). The blood samples were gathered in three phases: before, immediately and 30 minutes after the exercise in order to measure plasma volume, Interleukin 6, testosterone and cortisol. Results. The results showed that testosterone/cortisol (T/C) ratio was higher in Group 1 when compared with Group 2. It was also higher in Group 2 when compared with Group 3 (P<0.05). Plasma volume and Interleukin 6 (IL-6) were significantly lower and higher respectively in Group 3 when compared with Group 1 and 2 (P<0.05). Conclusion. It can be concluded that if beverages are not consumed in wrestling intervals, it may cause not only negative physiological and biochemical effects, but also mental pressure on wrestlers so their sport performance may be negatively affected.